Evaluation of Job Satisfaction and Job Related Stress Among Community Pharmacists in North Khartoum and its Impact on Providing Pharmaceutical Care Services - Azza Mohamed Tahir; Tarig Mohamed Hassan; Ali Awadallah Ali; Mazin Yousif Babiker; Mohamed Awad Mousnad (Journal of Advanced Pharmaceutical Science And Technology, 2019)
Introduction Pharmacists and pharmaceutical care services are among the most important tools in providing health services to the society. Pharmacists as the key players in presenting health services, critically impact on the health of the society and if they suffer low job satisfaction, their dissatisfaction may relatively threaten health in the society. This study was conducted to determine Sudanese community pharmacists’ job satisfaction and additionally, some causes of dissatisfaction among community pharmacists and their impact on providing pharmaceutical care services have been evaluated. Method The questionnaire was designed after reviewing relevant Literature in addition, The Job Satisfaction survey was used to measure the level of community pharmacists’ satisfaction with their current jobs, and the Toronto Alexithymia Scale (TAS-20) was used to evaluate emotional experience and awareness. Results and Discussion Generally low scores of job satisfaction were concluded among pharmacists while most of them were highly satisfied with being pharmacist. Conclusion Low levels of job satisfaction which were found among Sudanese community pharmacists could be considered as a deficiency of health system in Sudan. Fortunately, inherent interest in the pharmacy profession found among Sudanese pharmacists is an optimistic point at which policy-makers could develop their modifying policies. Health policy-makers must endeavor to take other steps to issue solutions for this current problem.
Keywords: job satisfaction